Investigation of Nonlinear Behavior of Concrete on Seismic Performance of an Arch Dam Using Finite Element Method - Mortaza Ali Ghorbani; Majid Pasbani Khiavi; Parya Ahmadi (Salehan Institute of Higher Education, 2016)
In this paper the effect of nonlinear behaviour of concrete is investigated on seismic performance of a double curvature concrete dam. The Morrow Point concrete dam has been selected as the case study and dam-reservoir-foundation interaction considered in the model. Finite element method has been used for modelling and analysis of case study by applying the El Centro earthquake components considering nonlinear behaviour of concrete. The obtained results of nonlinear dynamic analysis illustrate the increasing of displacement of dam crest along the river and decreasing of maximum principle stresses in critical points. The results demonstrate the importance of consideration of nonlinear behaviour of material in seismic performance of arch dams to achieve the optimal design of models.